ASSISTANCE IN IMPROVING NUTRITIONAL ASPECTS THROUGH THE MAKING OF HOMEMADE FEED FOR BELOVED PETS IN THE CITY OF MAKASSAR - AMRIANI, RINI; Dian Fatmawati; Muh. Zulfadillah Sinusi; DWI KESUMA SARI; A. Magfira Satya Apada (Universitas Airlangga, 2024)
This community service activity was carried out at the Hasanuddin University Animal Hospital with the aim of improving nutritional aspects through the assistance of homemade pet food preparation in Makassar City. The activity took place on Saturday, April 27, 2024, at the Hasanuddin University Animal Hospital, Makassar, South Sulawesi. The participants in this activity were 55 pet owners. The methods used in this activity began with a survey in the form of questionnaires given to pet owners regarding their understanding of pet nutrition. Another method was the transfer of knowledge, both in the form of instructional videos and pocket books on making balanced homemade pet food using ingredients readily available in the market. The results of this community service showed an increase in pet owners' understanding of pet nutrition based on the initial and final surveys conducted. The initial survey showed that 46 out of 53 respondents did not understand this nutritional aspect well, whereas the final survey showed that all 55 participants understood the importance of nutrition for their pets. Additionally, the use of easily obtainable ingredients in the market, such as mackerel, which is rich in macromolecules, vitamins, and minerals, was highlighted. The food formulation was measured according to the daily needs of the pets. The homemade pet food proved to be liked by the pets and economical, thereby enhancing the welfare of pet owners in Makassar City.